Palliative Care in Huntington Disease: Personal Reflections and a Review of the Literature - Tarolli, Christopher G; Chesire, Amy M; Biglan, Kevin M (Tremor and other hyperkinetic movements (New York, N.Y.), 2017)
Huntington disease is a fatal, autosomal dominant, neurodegenerative disorder manifest by the triad of a movement disorder, behavioral disturbances, and dementia. At present, no curative or disease modifying therapies exist for the condition and current treatments are symptomatic. Palliative care is an approach to care that focuses on symptom relief, patient and caregiver support, and end of life care. There is increasing evidence of the benefit of palliative care throughout the course of neurodegenerative conditions including Parkinson disease and amyotrophic lateral sclerosis. However, beyond its application at the end of life, little is known about the role of palliative care in Huntington disease. In this article, we discuss what is known about palliative care in Huntington disease, specifically related to early disease burden, caregiver burnout, advance care planning, and end of life care. We provide a review of the current literature and discuss our own care practices. We conclude by discussing questions that remain unanswered and positing ideas for future work in the field.